How Human Resource Practice, Perceived Organizational Support, and Job Embeddedness Influence Turnover Intention - Marcella, Bonitha Dame; Satrya, Aryana (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
This study focuses on the technology sector, a strategic area of the Indonesian economy. Technological developments encourage companies to retain their top tech employees. The objective of this study is to examine the impact that employees' perceptions of human resource practice and organizational support have on their level of job embedment and intention to leave their jobs. The current study also investigates the mediation effect of job embeddedness. An online survey utilizing a seven-point Likert scale was administered to 284 IT employees from diverse technology companies in Indonesia with a purposive sample technique. This study shows that human resource practice, organizational support perceived by employees, and job embeddedness are essential factors influencing turnover intention.